Globalisasi dan Pengembangan Kultur Pesantren di Bangka Belitung - Rasyid, Hatamar (Tawshiyah: Jurnal Sosial Keagaman dan Pendidikan Islam, 2016)
During this mode of schools identified with the culture of traditionalism, should at least be understood in two different ways. On one side of this traditionalism refers to a system rooted teachings of conspiracy marriage between theology skolatisisme Asy'ariyah with Maturidiyah with the teachings of Sufism (Islamic mysticism) which has been developed in Indonesia. While on the other side of traditionalism in teaching methodology (education) is applied in the world of pesantren (literacy salafiyah). The mention in the context of traditional teaching because in this case the pattern of teaching that monologues, not on Dialogic-emancipatory. The status and role of kiai become very dominant in-santrinya indoctrinate the students with a teaching approach that is both classic like; bandongan, sorogan, the market and so forth. This paper aims to explore the developmental stages Ponpes in the era of globalization and how they survive in conditions that suppressed by foreign cultures.